Literatur Review: Hubungan Caring Perawat dengan Kepuasan Pasien di Pelayanan Kesehatan - Nova -; Ranti Damayanti; Ridha Ghina; Satria Rifqi; Heri Ridwan; Ahmad Purnama (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2023)
Background: The attitude of respect and empathy when treating patients is commonly referred to as caring. This attitude is very important in determining patient satisfaction. Satisfaction is a feeling of pleasure or disappointment felt by someone in achieving the expected results against the performance carried out, if the performance is below expectations then the customer is not satisfied, and vice versa. Nursing services determine the quality of health services, because nurses are the ones who most often meet with patients. Purpose: This study focuses on finding out whether there is a relationship between nurses' caring attitude and patient satisfaction in health services. Methods: The research method used was a literature study. The Preferred Reporting Items for Systematic Reviews & Metaanalysis (PRISMA) procedure was used in this study, which resulted in 14 article analyses. The databases used in this study were Elsevier, Google Scholar, PUBMED and Taylor & Francis with inclusion criteria: Journals published from 2018 to 2023 using Indonesian and English, National and International Journals, Articles using quasi-experimental methods, pre-experimental design, case studies and full text articles. Result: Analysis of the 14 journals found by the researchers led to the conclusion that there is a relationship between patient satisfaction and caring behaviour by nurses in the health care system. Conclusion: It can be concluded from the analysis of these 14 research journals that the relationship between caring nurses and the level of patient satisfaction in the health care system has a very close relationship in it.